Gallagher Girls: I'd Tell you I Love You, But Then I'd Have to Kill You - Book 1 - Carter, Ally. (New York : Orchard Books., 2010)
As a sophomore at a secret spy school and the daughter of a former CIA operative, Cammie is sheltered from "normal teenage life" until she meets a local boy while on a class surveillance mission.
Keywords: Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Man-woman relationships; Juvenile fiction; Spy fiction